2007
DOI: 10.1097/01.mcg.0000225611.48728.1e
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis in Frail Elderly People

Abstract: These findings seem to substantiate the theory that esophagitis is a characteristic which exacerbates frailty in hospitalized elderly people and its identification may be helpful in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
5
1
1
Order By: Relevance
“…In addition, at present, it is not fully understood which additional risk factors contribute to the development of reflux esophagitis or what influence these factors might have on disease severity. Possible risk factors reported include overweight, male gender, history of GERD, smoking habit, absence of Helicobacter pylori or presence of hiatal hernia 1–3, 10–13 . As far as severe esophagitis is concerned, the clinical data suggest a relationship with severity of symptoms, presence of heartburn for more than five years, obesity, presence of hiatal hernia, male gender and Caucasian ethnicity 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, at present, it is not fully understood which additional risk factors contribute to the development of reflux esophagitis or what influence these factors might have on disease severity. Possible risk factors reported include overweight, male gender, history of GERD, smoking habit, absence of Helicobacter pylori or presence of hiatal hernia 1–3, 10–13 . As far as severe esophagitis is concerned, the clinical data suggest a relationship with severity of symptoms, presence of heartburn for more than five years, obesity, presence of hiatal hernia, male gender and Caucasian ethnicity 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Finally, the role of drugs in the pathogenesis of severe esophagitis is especially controversial and has been only partially evaluated. While the use of PPIs is considered to be a protective factor, 11,16 the role of other drugs such as anticholinergics, 17 nitrates 11,18 and tricyclic antidepressants, calcium antagonists or sulcralfate 11 is more debatable. In particular, the results of studies of the effect of nonsteroidal anti-inflammatory drugs (NSAIDs) have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, osteoporosis and sarcopenia were associated with frailty in a univariate analysis, so GERD symptom generation due to osteoporosis and sarcopenia may be related to the onset of frailty. Cardin et al reported that being bedridden was an independent risk factor for esophagitis, that esophagitis exacerbates frailty in hospitalized elderly people, and that its identification may be helpful in these patients ( 23 ). Therefore, the management of GERD symptoms may be important for the prevention of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Eine diagnostizierte Frailty anhand etablierter Frailty−Instru− mente beeinflusst weiter per se den Verlauf einer vorbestehen− den chronischen Erkrankung in negativer Weise. Dies gilt für die koronare Herzkrankheit [13], Schlaganfall [14], Alzheimer'sche Demenz [15], Morbus Parkinson [16], venöse Thrombosen [17] sowie die Ösophagitis [18]. Kürzlich konnte am Beispiel des Prostatakarzinoms und einer hormonsupprimierenden Therapie bei älteren Männern die sinnhafte Anwendbarkeit der Frailty−Diagnose für therapeuti− sche Indikationsstellungen aufgezeigt werden [19].…”
Section: Definitionen Von Frailtyunclassified